Modeling calcium waves in cardiac myocytes: importance of calcium diffusion. - Swietach, P; Spitzer, K; Vaughan-Jones, R (2010)
Under certain conditions, cardiac myocytes engage in a mode of calcium signaling in which calcium release from the sarcoplasmic reticulum (SR) to myoplasm occurs in self-propagating succession along the length of the cell. This event is called a calcium wave and is fundamentally a diffusion-reaction phenomenon. We present a simple, continuum mathematical model that simulates calcium waves. The framework features calcium diffusion within the SR and myoplasm, and dual modulation of ryanodine receptor (RyR) release channels by myoplasmic and SR calcium. The model is used to illustrate the effect of varying RyR permeability, sarco/endoplasmic reticulum Ca2+ ATPase (SERCA) activity and calcium ion mobility in myoplasm and SR on wave velocity. The model successfully reproduces calcium waves using experimentally-derived variables. It also supports the proposal for wave propagation driven by the diffusive spread of myoplasmic calcium, and highlights the importance of SR calcium load on wave propagation.